“They said over the phone to question this story where women are not present”: the role of women musicians in Rio de Janeiro’s samba in early twentieth century (Per Musi, 2013)
This research investigates the samba in Pequena África do Rio de Janeiro during the first decades of the 20th century in order to analyze the role of women in the process its formation. This is a musical world where women were devalued, obscured by a historical construct created by the upper classes, focused on the big men, on the major events in the supposedly more important field of public life and the written tradition, with no interest in the domestic face, in the oral tradition, and in the knowledge of women.